2019
DOI: 10.1136/bcr-2018-228293
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Addison’s disease with increased hydrocortisone requirements due to administration of rifampicin

Abstract: A 58-year-old man was referred to our hospital for darkened skin, general fatigue and weight loss. His adrenocorticotropic hormone and cortisol levels indicated a primary adrenal insufficiency. 18Fluorodeoxyglucose positron emission tomography/CT showed bilateral enlargement of the adrenal glands, with 18fluorodeoxyglucose accumulation. Loop-mediated isothermal amplification assays of bronchoalveolar lavage fluid were positive for Mycobacterium tuberculosis. The patient was diagnosed with tuberculous Addison’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Adverse reactions to anti-TB drugs and their interactions with corticosteroids that are administered for replacement therapy remain challenging[ 21 , 22 ]. Firstly, rifampicin increases cortisol catabolism while isoniazid produces increased levels of cortisol via an opposite effect on the enzyme activity 6-Bhydroxylase; secondly, hepatitis, induced by isoniazid and worsened by rifampicin, leads to failure of 11-B-oxo-reductase, which converts cortisone to cortisol; and finally, tuberculous Addison’s disease might require increased amounts of hydrocortisone due to rifampicin administration[ 23 ]. Up to 70% of patients with active TB have subclinical adrenal insufficiency[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions to anti-TB drugs and their interactions with corticosteroids that are administered for replacement therapy remain challenging[ 21 , 22 ]. Firstly, rifampicin increases cortisol catabolism while isoniazid produces increased levels of cortisol via an opposite effect on the enzyme activity 6-Bhydroxylase; secondly, hepatitis, induced by isoniazid and worsened by rifampicin, leads to failure of 11-B-oxo-reductase, which converts cortisone to cortisol; and finally, tuberculous Addison’s disease might require increased amounts of hydrocortisone due to rifampicin administration[ 23 ]. Up to 70% of patients with active TB have subclinical adrenal insufficiency[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some recommend to double or even triple the dose of adrenal steroids in patients with PAI (8). Others tend to use plasma cortisol levels 2 h after administration of the morning dose of hydrocortisone (9). A pharmacokinetic study of Rousseau et al showed a strong correlation between those levels and the daytime cortisol profile on a thrice daily regimen (9).…”
Section: Discussionmentioning
confidence: 99%
“…Others tend to use plasma cortisol levels 2 h after administration of the morning dose of hydrocortisone (9). A pharmacokinetic study of Rousseau et al showed a strong correlation between those levels and the daytime cortisol profile on a thrice daily regimen (9). Nevertheless, clinical monitoring of glucocorticoid replacement therapy in these cases is very important to avoid an Addison crisis (1).…”
Section: Discussionmentioning
confidence: 99%
“…2,5 There is existing literature discussing the effects of other strong CYP3A4 inducers (e.g., rifampin) on exogenous steroids; however, data related specifically to mitotane are limited. [9][10][11] This is especially true in the pediatric setting due to the rarity of ACC in this population. 4 It is interesting to note the rapidity with which this presumed interaction was noted in our case, with adrenal crisis developing 2 days after mitotane initiation.…”
Section: Exogenous Steroid Replacement In a Pediatric Patient With Ad...mentioning
confidence: 99%
“…Based on high urinary concentrations of 6β‐hydroxycortisol, a cortisol metabolite in the presence of mitotane, it has been estimated that mitotane results in rapid inactivation of more than 50% of exogenous hydrocortisone 2,5 . There is existing literature discussing the effects of other strong CYP3A4 inducers (e.g., rifampin) on exogenous steroids; however, data related specifically to mitotane are limited 9–11 . This is especially true in the pediatric setting due to the rarity of ACC in this population 4 .…”
mentioning
confidence: 99%